Dual Education: A methodology Used in the Professional Secretariat School for developing workplace competencies during 2023 - Ureña Hernández, Mariam (2024)
The Dual Professional Training Project of the Professional Secretarial School (ESP) of the National University since 2000 and is implemented in the diploma program of the two careers Commercial Education and Office Administration, which provide work spaces for students to acquire certified professional experience and, at the same time, develop labor and social competencies, through the combination of theory and practice. Continuous supervision of the participants is carried out, as well as interviews and focus groups to learn about the experiences of this modality in the year 2023, which were the acquisition of knowledge in the area of technology with the use of platforms, programs and databases; the execution of techniques through the development of document types and file management; and participation in areas complementary to their training, such as training and handling of confidential information, in addition to the skills put into practice, for example, teamwork, assertive communication and creativity. The teaching staff of the ESP has pedagogical training and experience in the technical area, necessary to complement the work developed by the tutors within the companies, which have the disposition and resources to participate in this modality.